Rear-view mirror navigation: pre-crisis management accounting and control practices in Iceland. (1st January 2012) - Rikhardsson, Pall; Karlsson, Thorlakur; Sigurjonsdottir, Thordis Arny; Hilmarsson, Sindri Thor
In the beginning of the 21st century the Icelandic economy experienced a historical expansion with the largest Icelandic companies multiplying in size many times over measured in turnover. Research shows that such immense growth is synonymous with great environmental uncertainty and turbulence. Theoretically, Icelandic companies should have developed more advanced management control systems in response to these conditions. However, as research conducted by the authors of this article shows, this was not the case. Icelandic companies had management control systems that were better suited to stability and unchanging environmental conditions, placing emphasis on financial budgets and simple costing methodologies, few internal controls and limited performance measurement systems. The adoption of more appropriate systems seems to have lagged behind the actual need for them. The reasons for this could include the relative size of Icelandic companies, lack of management knowledge of different management accounting and control systems and the dominant Icelandic business culture.